2020
DOI: 10.3390/rs12050858
|View full text |Cite
|
Sign up to set email alerts
|

A Synergetic Approach to Burned Area Mapping Using Maximum Entropy Modeling Trained with Hyperspectral Data and VIIRS Hotspots

Abstract: Southern European countries, particularly Spain, are greatly affected by forest fires each year. Quantification of burned area is essential to assess wildfire consequences (both ecological and socioeconomic) and to support decision making in land management. Our study proposed a new synergetic approach based on hotspots and reflectance data to map burned areas from remote sensing data in Mediterranean countries. It was based on a widely used species distribution modeling algorithm, in particular the Maximum En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
(73 reference statements)
3
17
0
Order By: Relevance
“…Being fundamentally distinct from other machine learning methods, MaxEnt uses presence-only dataset to train itself (Elith et al 2011). However, like many studies have shown earlier, the present study also indicated that this distinction of MaxEnt does not limit its capability in generating reliable hazard prediction maps (Arpaci et al 2014;Massada et al 2013;Peters et al 2013;Fonseca et al 2016;Kim et al 2015;Fernández-Manso and Quintano 2020;Lim et al 2017). In this study a limited set of features have been considered for forest re prediction.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Being fundamentally distinct from other machine learning methods, MaxEnt uses presence-only dataset to train itself (Elith et al 2011). However, like many studies have shown earlier, the present study also indicated that this distinction of MaxEnt does not limit its capability in generating reliable hazard prediction maps (Arpaci et al 2014;Massada et al 2013;Peters et al 2013;Fonseca et al 2016;Kim et al 2015;Fernández-Manso and Quintano 2020;Lim et al 2017). In this study a limited set of features have been considered for forest re prediction.…”
Section: Discussionsupporting
confidence: 78%
“…Studies indicate that MaxEnt has performed equally well in comparison to other machine learning methods in predicting a forest re. (Arpaci et al 2014;Massada et al 2013;Peters et al 2013;Fonseca et al 2016;Kim et al 2015;Fernández-Manso and Quintano 2020;Lim et al 2017) In this study, MaxEnt has been applied to prepare a forest re prediction map of Sikkim Himalaya using MODIS and Ground data-based forest re inventory. As features, meteorological, topological, ecological and human-induced data have been used to train the MaxEnt model.…”
Section: Introductionmentioning
confidence: 99%
“…Being fundamentally distinct from other machine learning methods, MaxEnt uses presence-only dataset to train itself (Elith et al, 2011). However, like many studies have shown earlier, the present study also indicated that this distinction of MaxEnt does not limit its capability in generating reliable hazard prediction maps (Arpaci et al, 2014;Fernández-Manso & Quintano, 2020;Fonseca et al, 2016;Kim et al, 2015;Lim et al, 2017;Massada et al, 2013;Peters et al, 2013). In this study a limited set of features have been considered for forest re prediction.…”
Section: Discussionsupporting
confidence: 48%
“…Studies indicate that MaxEnt has performed equally well in comparison to other machine learning methods in predicting a forest re. (Arpaci et al, 2014;Fernández-Manso & Quintano, 2020;Fonseca et al, 2016;Kim et al, 2015;Lim et al, 2017;Massada et al, 2013;Peters et al, 2013) In this study, MaxEnt has been applied to prepare a forest re prediction map of Sikkim Himalaya using MODIS and Ground data-based forest re inventory. As features, meteorological, topological, ecological, in-situ and human-induced data have been used to train the MaxEnt model.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the impact of the PB on the accuracy of a BA classified map, the area enclosed by it (the Area Under the Pareto Boundary, AUPB) was calculated, by analogy with the area of the ROC (Receiver Operating Characteristic) curve used in other burned area studies using machine learning or data mining [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The ROC curve is a probability curve constructed from sensibility and 1-specificity pairs {(S i ,1-Sp i )}, obtained using a procedure similar to that of the PB, and the area enclosed by it, the Area Under the ROC Curve (AUC), is interpreted as a measure of the separability between the two classes considered from the selected p parameter.…”
Section: Methodsmentioning
confidence: 99%